2009
DOI: 10.1558/imre.v11i3.265
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality—the emergence of a working definition for use within healthcare practice

Abstract: ^Southern Health and Social Care TrustCorrespondence to: c.mayersl@yorksj.ac.ukConsiderations of a person's spirituality and/or spiritual needs are necessary in order to provide holistic and person-centred intervention within healthcare. However, the term "spirituality" is difficult to define clearly, so healthcare professionals are often unsure as to what exactly spiritual needs are, and also what their role is in addressing these. An in-depth literature review was therefore carried out in order to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
1
6
0
1
Order By: Relevance
“…This agrees with research conducted with patients and carers who identified faith and beliefs as key components of spirituality (Ross 2006). The definitions chosen for the questionnaire in the study here took into account a consensus from the literature (including Koenig 2007;Mayers and Johnston 2008;Ozbasaran et al 2011;Ross 2006;Young and Koopsen 2011) over the components of spirituality.…”
Section: Definitionssupporting
confidence: 73%
See 1 more Smart Citation
“…This agrees with research conducted with patients and carers who identified faith and beliefs as key components of spirituality (Ross 2006). The definitions chosen for the questionnaire in the study here took into account a consensus from the literature (including Koenig 2007;Mayers and Johnston 2008;Ozbasaran et al 2011;Ross 2006;Young and Koopsen 2011) over the components of spirituality.…”
Section: Definitionssupporting
confidence: 73%
“…1;Koenig et al 2012, Ch. 2;Mayers and Johnston 2008;Miller and Thoresen 2003;Ross 2006;Swinton 2012). Other studies have also included a definition for the same reason (Collins et al 2001;Farrar 2001;Rose 1999) or have recommended the use of definitions (Engquist et al 1997;Johnston and Mayers 2005).…”
Section: Definitionsmentioning
confidence: 99%
“…What is left is, as Mayers and Johnston (2008) say, a 'highly subjective concept'. They conclude: 'The lack of consensual definition has not only created confusion for healthcare practitioners, but it has also caused widespread debates regarding the nature of spirituality and its relationship to religion, disability and occupational performance' (Mayers and Johnston 2008: 272).…”
Section: Introductionmentioning
confidence: 99%
“…Having a spiritual attitude helps to gain a different perspective on a situation, to transcend adverse circumstances, to (re-)connect with self, others, nature, and -for many -God or a Higher Power (Coyle, 2001;Mayers & Johnston, 2008). Connectedness and belonging are core aspects of the spiritual outlook (Emmett, 2008;Iwasaki, Bartlett, Gottlieb, & Hall, 2009;Shih et al, 2009).…”
Section: Health Benefits Of Spiritualitymentioning
confidence: 99%
“…Spiritual coping being a multidimensional construct, it was necessary to include a range of questions in order to access the various dimensions, e.g. transcendence, belonging, connectedness/unity, relationship with self, others, the world and a higher being, meaning and purpose, hope, and self-awareness (Coyle, 2001;Danesh, 1997;Mayers & Johnston, 2008;Pargament, 1999;Tanyi, 2002).…”
Section: Initial Scs-45mentioning
confidence: 99%